Strategy for Reducing Postpartum Hemorrhage Incidence Through the Implementation of Digital-Based Admission Screening: An Action Study in Hospitals - Isnia Maulidah; Feny Silviani (Eduvest - Journal of Universal Studies, 2026)
Postpartum hemorrhage (PPH) remains the leading cause of maternal mortality globally, including in Indonesia, where it accounts for 30.3% of maternal deaths. While PPH often occurs suddenly, its risk can be predicted at the time of hospital admission through systematic screening. However, the effectiveness of such screening depends on healthcare worker compliance, which can be hindered by administrative burdens. This study aims to evaluate the effectiveness of implementing a digital-based PPH admission screening tool in improving staff compliance and reducing PPH incidence at Muhammadiyah Gresik Hospital. Using an action research methodology under the Plan-Do-Study-Act (PDSA) framework, the study was conducted in two cycles. Cycle 1 employed a manual (paper-based) screening form, while Cycle 2 introduced a fully digital format. The study population included all maternity patients admitted during the intervention periods, with total sampling applied. Data were collected through direct observation, medical record audits, and hospital quality reports, and analyzed descriptively by comparing compliance and PPH rates across cycles. The findings indicate that the transition to a digital format significantly increased staff compliance from 89% in Cycle 1 to 100% in Cycle 2. Importantly, this improvement in compliance was directly associated with a reduction in PPH incidence from 3% at baseline to 1% post-digital intervention. The study concludes that digital-based admission screening serves as a crucial cognitive aid for strengthening risk management and advancing toward the zero-preventable-harm patient safety target.